(untitled) (Ustozlar uchun, 2025)
This article provides a systematic overview of the scientific research process, its nature, and all the essential stages involved. The study discusses the essence of scientific research, problem formulation, defining objectives and tasks, selecting research methods, data collection, and perspective. Furthermore, the research emphasizes how correct execution of each stage contributes to reiable and valid results.[1]